PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF FISIKA SISWA SMA NEGERI 1 TAMBUSAI - ningsih, julia eva (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
This research discusses the effect of applying inquiry learning model to improve student learning outcomes cognitive physics SMA Negeri 1Tambusai. Population in this research is class XI IPA SMAN 1 Tambusai, while its sample are whole classes IX IPA as many as 50 students of SMAN 1 Tambusai. Data were analyzed using the test N-Gain. Results from termormalisasi cloth, with a value - average gain of 0.71 experimental class with high category, while the value - average gain of 0.53 with the control class medium category. Further testing the hypothesis using the t test. Before performing a hypothesis test conducted prerequisite test that uses test Liliefors normality test and homogeneity test using the F test, the result is a class of data samples have normal distribution and variance homogeneity. The next hypothesis test, the calculation results obtained by thitung = 4.05 and table = 2,021. This shows that thitung > table (Î± = 0.05). Itâs can be conclution thus there is the influence of inquiry learning model to the cognitive learning physics students SMA Negeri 1 Tambusai.